STUDI DESKRIPTIF PSYCHOLOGICAL WELL-BEING PADA MAHASISWA TAHUN PERTAMA PRODI X DAN IMPLIKASI DALAM BIMBINGAN DAN KONSELING - Rahman, Fadhila (Institut Daarul Qur'an Jakarta, Indonesia, 2020)
Many demands of academic activity for students is difficulity for the college life. It has can be impacted for physical and psychological conditions that will be associated with psychological well-being students. The purpose of this study is to describing psychological well-being of students by using descriptive methods. The population consisted of 78 students and using purposive sampling techniques. The data in inventory consisting of 50 statement adaptation items from Ryff and Keyes. Results showed that the majority (69%) of students had psychological well-being, with characteristics not fully capable of accepting weaknesses or strengths, having a warm relationship with others, being able to make decisions independently, being able to master and manage the environment, having direction and purpose in life, and have a desire that continues to grow. Furthermore, it is spread in the high (14%) and low category (17%). The results of the study can be used as a reference for counselors in University to provide guidance and counseling services such as group guidance to improve student psychological well-being with developments to the needs and characteristics of the students.